Effect of gloved hand disinfection on hand hygiene before infection-prone procedures on a stem cell ward. Issue 3 (November 2019) - Fehling, P.; Hasenkamp, J.; Unkel, S.; Thalmann, I.; Hornig, S.; Trümper, L.; Scheithauer, S.
Summary: Background: Hand hygiene compliance even before infection-prone procedures (indication 2, 'before aseptic tasks', according to the World Health Organization (WHO)) remains disappointing. Aim: To improve hand hygiene compliance by implementing gloved hand disinfection as a resource-neutral process optimization strategy. Methods: We performed a three-phase intervention study on a stem cell transplant ward. After baseline evaluation of hand hygiene compliance (phase 1) gloved hand disinfection was allowed (phase 2) and restricted (phase 3) to evaluate and differentiate intervention derived from learning and time effects. The incidence of severe infections as well as of hospital-acquired multidrug-resistant bacteria was recorded by active surveillance. Findings: Hand hygiene compliance improved significantly from 50% to 76% ( P < 0.001) when gloved hand disinfection was allowed. The biggest increase was for infection-prone procedures (WHO 2) from 31% to 65%; P < 0.001. Severe infections decreased by trend (from 6.0 to 2.5 per 1000 patient-days) whereas transmission of multidrug-resistant organisms was not affected. Conclusion: Gloved hand disinfection significantly improved compliance with the hand hygiene, especially in activities relevant to infections and infection prevention. Thus, this process optimization may be an additional, easy implementable, resource-neutral tool for a highly vulnerable patient cohort.